Contesting the term 'compassion fatigue': Integrating findings from social neuroscience and self-care research. Issue 2 (April 2020) - Hofmeyer, Anne; Kennedy, Kate; Taylor, Ruth
Abstract: Background: Nurses describe work-related distress and exhaustion as compassion fatigue and burnout. However, neuroscientists confirm compassion does not cause fatigue. Aim: This discussion paper explains contemporary social neuroscience evidence about empathy, emotion regulation, and compassion, then discusses evidence-informed strategies to cultivate effective self-care practices and compassion. Methods: The argument draws on relevant empirical evidence and literature to raise awareness, improve understanding, and spark dialogue and reconceptualisation of these critical issues within the nursing context. Findings and discussion: Functional magnetic resonance imaging studies show the debilitating condition known as compassion fatigue should be called 'empathic distress fatigue'. This distinction matters because the strategy to ease empathic distress fatigue is compassion training. The capacity to remain clear about the 'self-other' distinction is called emotion regulation. Without emotion regulation skills, our 'self-other' distinction is blurred so we absorb another's suffering and negative emotions as our own and experience empathic distress fatigue. Yet, much of this knowledge is not implemented within the nursing context. On the contrary, the topic of compassion fatigue continues to dominate education and research. This knowledge gap is significant because healthcare leaders cannot address the distress of its workforce and strengthen cultures without understanding its causes. Conclusion: Evidence from social neuroscience and self-care studies offers promising new knowledge to design strategies to foster self-care, self-compassion, emotion regulation, and ease empathic distress fatigue. These strategies and practices for renewal support the raison d'être of nursing which is to provide quality, safe, compassionate care for patients and their families by resilient nurses.